Obesity and asthma: co-morbidity or causal relationship? - van Huisstede, A.; Braunstahl, G.J. (Monaldi Archives for Chest Disease, 2016)
There is substantial evidence that obesity and asthma are related. â€œObese asthmaâ€ may be a unique phenotype of asthma, characterized by decreased lung volumes, greater symptoms for a given degree of lung function impairment, destabilization or lack of asthma control, lack of eosinophilic inflammation and a different response to controller medication. Whether this relationship between obesity and asthma is causal or represents co-morbidity due to other factors is unclear. In previous reviews concerning the relationship between obesity and asthma, five hypotheses were put forth. One of these hypotheses is that a low grade systemic inflammation caused by adipokines from the fat tissue causes or enhances bronchial inflammation. In animal models, there is an increasing amount of evidence for the role of adipokines derived from fat tissue in the relationship between obesity and asthma. The data are conflicting in humans. Since obesity is a component of the metabolic syndrome and the metabolic syndrome is also a form of systemic inflammation, it is to be expected that there is a relationship between metabolic syndrome and asthma. The few data that are available show that there is no relationship between metabolic syndrome and asthma, but there is one between the metabolic syndrome and asthma-like symptoms. Further research is needed to confirm the relationship between obesity and asthma in humans, where a rigorous approach in the diagnosis of asthma is essential.